The Composition of Essential Oils and the Content of Saponins in Different Parts of Gilia capitata Sims - Ain Raal; Jaan Liira; Martin Lepiku; Tetiana Ilina; Alla Kovalyova; Pavel Strukov; Andriy Gudzenko; Oleh Koshovyi (Crops, 2025)
Bluehead gilia or bluefield gilia (Gilia capitata Sims, Polemoniaceae) is an annual herbaceous plant widely distributed in the western regions of North America but cultivated as an ornamental flower in various regions to support pollinators. The comprehensive chemical composition of this plant has not been previously reported. Essential oils (EOs) were obtained by hydrodistillation from different parts of the gilia plants. The yield of EOs ranged from 0.42 to 1.97 mL/kg, with the largest yields being obtained from the seeds; smaller yields obtained from the flowers, fruits, and leaves; and the lowest quantity obtained from the stems, roots, and shells. Using the GC-MS method, we identified 116 compounds. Hexahydrofarnesyl acetone was dominant in most parts of the G. capitata. The EO of flowers was dominated by hexahydrofarnesyl acetone (19.1%), fruits by hexahydrofarnesyl acetone (18.2%), seeds by hexahydrofarnesyl acetone (15.2%), fruit by (+)-epi-bicyclosesquiphellandrene (15.4%), leaves by phytol (23.3%), stems by isomanool (8.3%), and roots by (-)-myrtenol (25.7%). Triterpenoid saponins were identified, and 21 compounds were quantified (by HPLC). Saponin levels were high in aerial parts (excluding stems) and the lowest in plant roots. Based on the contents of EO and saponins, the aerial parts of G. capitata may have pharmaceutical properties, but saponins might be the main value of G. capitata.